Oculoplastic Surgery Atlas Cosmetic Facial Surgery (Springer International Publishing, 2018)
When the first edition of this atlas was published in 2005, it was well received throughout the oculoplastic and ophthalmology community for its simplicity and clinical focus. Now, a decade later, surgical techniques have been updated to reflect current practice models and advances in technology. The field of oculoplastic surgery has grown and evolved to include all aspects of facial plastic surgery and the literature must now reflect the advancements of this field. Oculoplastic Surgery Atlas: Cosmetic Facial Surgery, 2nd edition combines text and diagrams, plus surgical videos that enable readers to perform this surgery with the best possible instruction and preparation. Written for ophthalmology specialists and residents, this new edition presents many aspects of facial cosmetic surgery, including blepharoplasty, endoscopic forehead surgery, rhytidectomy, and soft tissue and lip augmentation. Review of the previous edition: "The book offers insight into the possibilities and technology of modern aesthetic cosmetic surgery in the face region. ... The book can be recommended for the aesthetic surgeon and for ophthalmologists. ... The ophthalmologic plastic surgeon will find this book of interest especially in showing a lot of additional possibilities and dimensions in this field. The book will be an asset in every ophthalmic surgeons library." (Karl-Heinz Emmerich, Graefe's Archiv for Clinical and Experimental Ophthalmology, Vol. 245, 2007).